Human Pluripotent Stem Cell-Derived Neural Crest Cells for Tissue Regeneration and Disease Modeling - Srinivasan, Akshaya; Toh, Yi-Chin (Frontiers in Molecular Neuroscience, 2019)
Neural crest cells (NCCs) are a multipotent and migratory cell population in the developing embryo that contribute to the formation of a wide range of tissues. Defects in the development, differentiation and migration of NCCs give rise to a class of syndromes and diseases that are known as neurocristopathies. NCC development has historically been studied in a variety of animal models, including xenopus, chick and mouse. In the recent years, there have been efforts to study NCC development and disease in human specific models, with protocols being established to derive NCCs from human pluripotent stem cells (hPSCs), and to further differentiate these NCCs to neural, mesenchymal and other lineages. These in vitro differentiation platforms are a valuable tool to gain a better understanding of the molecular mechanisms involved in human neural crest development. The use of induced pluripotent stem cells (iPSCs) derived from patients afflicted with neurocristopathies has also enabled the study of defective human NCC development using these in vitro platforms. Here, we review the various in vitro strategies that have been used to derive NCCs from hPSCs and to specify NCCs into cranial, trunk and vagal subpopulations and their derivatives. We will also discuss the potential applications of these human specific NCC platforms, including the use of iPSCs for disease modeling and the potential of NCCs for future regenerative applications.